How is parental psychological control associated with adolescent mental health in economically disadvantaged areas? The serial mediating role of psychological reactance and problematic smartphone use - Li, Qiangqiang; Wei, Shuwen; Liu, Zixiao (Frontiers in Psychiatry, 2024)
Adolescent mental health has been an issue of global concern, and the mental health of adolescents in economically disadvantaged areas may require additional research. The research delves into factors associated with economically disadvantaged areas' adolescent mental health, employing family systems theory, self-determination theory, and psychological reactance theory. Specifically, the present study which was done in Jingzhou country, an economically disadvantaged area of Hunan Province, China, aimed to examine the link between parental psychological control and adolescent mental health, as well as the mediating roles of psychological reactance and problematic smartphone use in this relationship. A sample of 1300 Chinese middle school students (620 girls, mean age = 14.22 ± 1.29) completed self-reported measures of parental psychological control, psychological reactance, problematic smartphone use, and adolescent mental health. Results showed that parental psychological control was negatively associated with adolescent mental health. Psychological reactance and problematic smartphone use mediated the association between parental psychological control and adolescent mental health, separately and serially. The findings of the present study enrich the literature on parenting styles and adolescent mental health in economically disadvantaged areas, and this provides an intervention perspective to reduce the negative impact of poor parenting on adolescent mental health in economically disadvantaged areas.